Data System Management in Mahogany Tree Seedlings (Swietenia mahagoni) Based on Website. - Aviana, Ais; Hartanti, Dyah Ayu Sri (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Mahogany tree nurseries or similar tree nurseries require a long process to develop in the furniture industry. The management system used so far is still done manually, namely using some bookkeeping and even imagining the process of growing the tree. Farmers who breed selectively felled trees such as mahogany trees really need an information system that supports systematic and easy data processing. For this reason, the author is trying to make a Final Project using a web-based system regarding processing nursery data, which until now has not been computerized. This web-based system was written to simplify the process of managing nursery data so that the plant process is transferred to make it more effective and efficient in supporting activities. The author designed a web-based sales application information system using the PHP, HTML and JavaScript programming languages. The method used in designing software for sales applications is the waterfall method, data collection techniques, observations and interviews. This information system design is the best solution to solve the problems that exist in this company. A computerized system is better than a conventional system, because a computerized system can run more safely than the system used previously.